An object-oriented knowledge-based expert system for fault diagnosis of a steam power station - Qureshi, Muhammad Shahid; Batanov, Dentcho N.; Nagarur, Nagendra N.; Huynh, Ngoc Phien; Government of Netherland (Bangkok : Asian Institute of Technology, 1994)
A prototype knowledge based condition monitoring and diagnostic system has been developed to act as an operational and diagnostic aid to operators of steam power plants. This system enables abnormal and inefficient operating conditions such as high vibration, high value of thermal expansion in steam turbines to be detected and diagnosed. Some special features of the system include the simulation of the power plant process within a specified range of normal and abno1mal conditions. The whole system is implemented on a P.C using object oriented development environment and an expert system shell. The work investigates how knowledge can efficiently be represented and administered using both an object oriented development environment and an expert system shell. The knowledge acquired for the expert system has been coded in the form of objects, rules and formula. Efforts have been made to make the representation and reasoning structures and methods as generic as possible so that similar systems for other power plants can be developed with minimal effort.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Expert systems (Computer science); Object-oriented data bases